Cardio-ankle vascular index (CAVI) measured by a new device: protocol for a validation study - Sergio Rico Martín; Valentina Vassilenko; Jorge M de Nicolás Jiménez; Purificación Rey Sánchez; Andreia Serrano; Mariana Martínez Alvarez; Julián F Calderón García; Juan F Sánchez Muñoz-Torrero (BMJ Open)
Introduction Cardio‐ankle vascular index (CAVI) is a new marker of arterial stiffness (AS) that can assess vascular wall stiffness in the aorta, femoral artery and tibial artery. CAVI is less affected by blood pressure at the time of measurement than the gold standard method (carotid-femoral pulse wave velocity (PWV)). Our group has developed a device called VOPITB (Velocidad Onda de Pulso Índice Tobillo Brazo) that uses the oscillometric method and easily and accurately measures the PWV in the arms and legs separately, allowing new AS indices to be studied. This article describes the research protocol to determine CAVI using VOPITB and to validate the device against a reference device (VaSera VS-1500) and assess its clinical utility.Methods and analyses A cross-sectional, descriptive and observational study will be conducted. In all, 120 subjects (a minimum of 40% of subjects from any one gender) will be evaluated. CAVI will be determined from the measurement by VOPITB and VaSera VS-1500. For each subject, the average of the three readings taken with each device will be calculated. The Bland-Altman plot will be used to determine whether any bias exists in the data—that is, a tendency of the size of the difference to vary with the mean. The participants will be divided roughly equally between the following age bands: <30, 30–60 and >60 years.Ethics and dissemination The study has been approved by the ethics committee of the Hospital San Pedro de Alcántara, Cáceres, Spain. The participants will be required to sign an informed consent form before inclusion in the study, in accordance with the Declaration of Helsinki and WHO standards for observational studies. The dissemination plan of the research study results will be through presentations in relevant national and international conferences and scientific publications in peer-reviewed journals.Trial registration number NCT04303546.